Wear-resistant and antibacterial school uniform fabric based on polyester fibers and graphene and preparation process of wear-resistant and antibacterial school uniform fabric

By combining modified graphene nanosheets with polyester fibers and adding other auxiliary agents to form a new wear-resistant and antibacterial school uniform fabric, the limitations of existing polyester fibers in terms of antibacterial and wear resistance are solved. The versatility of the fabric has been improved.

CN119433796APending Publication Date: 2025-02-14JIANGSU HAVLIN GARMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411780510.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing polyester fibers have limitations in antibacterial and wear resistance, and it is difficult to meet the application needs of certain special fields.

Method used

By combining the modified graphene nanosheets with polyester fibers, antibacterial agents, dispersants, antioxidants, stabilizers, softeners and crosslinkers, a new wear-resistant and antibacterial school uniform fabric is formed. The modified graphene nanosheets are synthesized and chimerized by titanium dioxide as particle media to form frame particles on the surface and sides of the nanosheet, improving the antibacterial and wear resistance of the fabric.

Benefits of technology

It significantly improves the wear resistance, antibacterial, moisture-absorbing, aging resistance and corrosion resistance of the fabric, extends the service life of the clothing, and enhances the mechanical properties of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172663100000151
    Figure BDA0005172663100000151
Patent Text Reader

Abstract

The invention relates to the field of spinning, in particular to a wear-resistant and antibacterial school uniform fabric based on polyester fibers and graphene and a preparation process of the wear-resistant and antibacterial school uniform fabric. The wear-resistant and antibacterial school uniform fabric based on polyester fibers and graphene is prepared from the following raw materials in parts by mass: 60-80 parts of polyester fibers, 2-6 parts of modified graphene nanosheets, 0.3-0.8 part of an antibacterial agent, 2-4 parts of a dispersing agent, 0.5-1 part of an antioxidant, 1-2 parts of a stabilizer, 1-3 parts of a softening agent, 2-4 parts of a cross-linking agent and 5-15 parts of carbon fibers. The wear-resistant and antibacterial school uniform fabric based on the polyester fibers and the graphene has good wear resistance and antibacterial performance, the moisture absorption and sweat releasing performance, the aging resistance, the corrosion resistance and the like of the fabric can be further improved, the requirements of consumers for existing textiles are effectively met, more functions are achieved, and the application prospect is quite excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of textiles, and in particular to a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene and a preparation process thereof. Background Art

[0002] With the development of technology and the changes in consumer demand, textiles not only need to meet basic wearing comfort requirements, but also gradually incorporate more functional requirements, such as wear resistance, antibacterial properties, etc. Especially in the fields of medical health, sports and leisure, the demand for antibacterial, deodorizing, wear-resistant and other functions is increasing.

[0003] Polyester fibers have been widely used in the textile industry due to their excellent physical properties (such as high strength, good elasticity, corrosion resistance) as well as good processability and dyeability. However, ordinary polyester fibers have certain limitations in terms of antibacterial and wear resistance, which limits their application in some special fields. In recent years, graphene, as a new type of two-dimensional material, has shown great application potential in many fields due to its unique physical and chemical properties (such as high strength, good conductivity, high thermal stability, etc.). Introducing graphene into textiles can not only significantly improve the physical properties of the fabric, such as improving wear resistance and conductivity, but also give the fabric new functional properties, such as antibacterial and UV protection.

[0004] Combining the advantages of polyester fiber and graphene, developing a new type of antibacterial and wear-resistant fabric has become one of the research hotspots. This fabric can not only effectively resist the growth and reproduction of bacteria and reduce odor, but also maintain high wear resistance and extend the service life of clothing. In addition, through appropriate treatment methods, the feel, breathability and moisture absorption and perspiration performance of the fabric can be further optimized to make it more in line with the requirements of ergonomic design.

[0005] Therefore, in order to provide a wear-resistant and antibacterial school uniform fabric with higher stability, stronger perspiration and moisture absorption, better aging and corrosion resistance, and better pilling resistance, the present application provides a fabric based on polyester fiber and graphene and a preparation method thereof. The fabric material finally prepared by the present application can effectively meet consumers' demand for existing textiles, has more functionality, and has very excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene. The raw materials are, by mass: 60 to 80 parts of polyester fiber, 2 to 6 parts of modified graphene nanosheets, 0.3 to 0.8 parts of antibacterial agent, 2 to 4 parts of dispersant, 0.5 to 1 part of antioxidant, 1 to 2 parts of stabilizer, 1 to 3 parts of softener, 2 to 4 parts of cross-linking agent, and 5 to 15 parts of carbon fiber.

[0007] As a preferred solution, the mass ratio of the polyester fiber, the modified graphene nanosheets and the carbon fiber is (70-75): (4-5.5): (8-10).

[0008] As a preferred solution, the mass ratio of the modified graphene nanosheet, the dispersant and the cross-linking agent is (4-5.5): (2.5-3): (3-3.5).

[0009] As a preferred solution, the polyester fiber has a fineness of 0.5 to 1.5 denier.

[0010] As a preferred solution, the polyester fiber has a fineness of 0.6 to 0.8 denier.

[0011] As a preferred solution, the average length of the polyester fiber is 30 to 60 mm.

[0012] As a preferred solution, the average length of the polyester fiber is 40 to 50 mm.

[0013] As a preferred solution, the cross-section of the polyester fiber is a Y-shaped cross-section or a pentagonal cross-section.

[0014] As a preferred solution, the cross section of the polyester fiber is a pentagonal cross section.

[0015] As a preferred solution, the preparation method of the modified graphene nanosheets specifically includes the following steps: S1: adding the graphene nanosheets and titanium dioxide to a DMF solution, heating to 70-75°C, adding succinic anhydride and keeping the temperature for 2-3 hours, washing, filtering and drying to obtain pretreated nanosheets; S2: adding titanium dioxide and anhydrous aluminum chloride to a mixed solution of DMF and deionized water, stirring at 100-120 rpm for 10-15 minutes, and then adding terephthalic acid and 2-aminoterephthalic acid. The mixed DMF solution of the acid is stirred at 100-120 rpm for 10-15 minutes to form a uniform solution, the reaction container is sealed, the temperature is raised to 130-150° C. under nitrogen protection, and the reaction is kept warm for 14-16 hours; S3: After the reaction is completed, it is naturally cooled to 70-80° C., and then the pretreated nanosheets are added, and the temperature is kept warm for 4-6 hours. After the reaction is completed, triethanolamine is added to adjust the pH value to 7.5-8, and then the product is filtered, washed with deionized water and acetone for 2-3 times, and then vacuum dried at 70-80° C. to complete.

[0016] As a preferred solution, in S1, the mass ratio of graphene nanosheets, titanium dioxide and succinic anhydride is (6-8): (0.8-1.4): (1.5-2).

[0017] As a preferred solution, in S2 and S3, the mass ratio of titanium dioxide, anhydrous aluminum chloride, terephthalic acid, 2-aminoterephthalic acid and pretreated nanosheets is (0.5-0.8): (2.5-3.5): (1.4-2): (1-1.4): (1-2).

[0018] As a preferred solution, in S2 and S3, the mass ratio of titanium dioxide, anhydrous aluminum chloride, terephthalic acid, 2-aminoterephthalic acid and pretreated nanosheets is (0.6-0.7): (2.5-3): (1.4-1.8): (1.1-1.3): (1-1.5).

[0019] As a preferred solution, the average particle size of the titanium dioxide is 10 to 20 nm.

[0020] As a preferred solution, in the mixed solution of DMF and deionized water, the mass ratio of DMF to deionized water is (2-3):1.

[0021] As a preferred solution, the number of layers of the graphene nanosheets is 5 to 10.

[0022] As a preferred solution, the lateral size of the graphene nanosheet is 3 to 5 μm.

[0023] In this application, by adding the modified graphene nanosheets, not only the wear-resistant and antibacterial properties of the fabric material are effectively improved, but also its moisture absorption and perspiration, aging resistance and corrosion resistance can be greatly improved. The modified graphene nanosheets added can form the synthesis and intercalation of framework particles on the surface and side of the nanosheets through the group action with titanium dioxide as the particle medium, so as to realize the sheet-like composite structure based on the graphene nanosheets, and the existence of the structure can form a good heterojunction structure, under the illumination environment, it can promote the titanium dioxide particles on the surface to form more hole-electron pairs, and can widen the bandgap length by extending the moving path of the electrons, so as to make the holes and electrons gather for a long time, not only greatly improve its oxidation antibacterial properties, but also avoid the backflow of electrons, so as to obtain excellent long-term antibacterial effect in the long-term use process, especially the addition of short-cut carbon fiber more obviously improves this effect, and the line-surface composite structure formed greatly enhances its connection force under the action of external force, so as to realize the improvement of the mechanical properties of the fabric. The modified graphene nanosheet composite structure formed has good structural stability, especially the addition of framework particles, which serve as surface supporting sites and have extremely excellent intermolecular structural stability, thereby always maintaining excellent overall orderliness of the molecular structure of the fabric surface in a long-term wear-resistant environment, thereby obtaining excellent wear-resistant performance.

[0024] On the other hand, the modified graphene nanosheets added in the present application can also form a guiding path for water molecules through the selected specific dispersants and chopped carbon fibers. The dispersants can enhance the surface stability of the modified graphene nanosheets and chopped carbon fibers in the mixed fabric, and when in contact with water, a large number of surface hydrophilic groups can be used to guide and adsorb water, and the more complex peak-to-valley surface can form grooves to lock the surface moisture and limit its migration effect, thereby achieving a continuous hydration layer area, accelerating the passage of moisture, and effectively achieving moisture absorption and perspiration, with excellent hygroscopicity; and the addition of carbon fibers can greatly enhance the surface free radical activity of the modified graphene nanosheets, and limit the penetration of active groups in the fabric coating, thereby effectively protecting the fibers and obtaining excellent aging resistance and corrosion resistance.

[0025] As a preferred solution, the antibacterial agent is at least one of silver chloride, zinc oxide, cetyltrimethylammonium bromide, potassium sorbate and sodium benzoate.

[0026] As a preferred solution, the antibacterial agent is hexadecyltrimethylammonium bromide.

[0027] As a preferred solution, the dispersant is a composition of polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine.

[0028] As a preferred solution, the mass ratio of the polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine is (6-10): (2-4): (2-4).

[0029] As a preferred solution, the mass ratio of the polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine is (8-9): (2.5-3): (3.5-4).

[0030] As a preferred solution, the hydroxyl value of the lauryl alcohol polyoxyethylene ether is 160-190 mgKOH / g.

[0031] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168 or antioxidant 626.

[0032] As a preferred solution, the antioxidant is antioxidant 1010 or antioxidant 1076.

[0033] As a preferred solution, the stabilizer is a combination of dibutyltin dilaurate and UV-531.

[0034] As a preferred solution, the mass ratio of dibutyltin dilaurate to UV-531 is (3-5): (1-1.5).

[0035] As a preferred solution, the mass ratio of dibutyltin dilaurate to UV-531 is (3.8-4.2):(1.2-1.4).

[0036] As a preferred solution, the softener is a composition of hexadecyltrimethylammonium chloride, aminosilicone oil and glyceryl stearate.

[0037] As a preferred solution, the mass ratio of hexadecyltrimethylammonium chloride, aminosilicone oil and glyceryl stearate is (1-1.5):(5-6):(0.3-0.5).

[0038] As a preferred solution, the crosslinking agent is a combination of diphenylmethane diisocyanate, toluene diisocyanate and γ-aminopropyltriethoxysilane.

[0039] As a preferred solution, the mass ratio of diphenylmethane diisocyanate, toluene diisocyanate and γ-aminopropyltriethoxysilane is (4-5): (2-3): (0.2-0.6).

[0040] As a preferred solution, the mass ratio of diphenylmethane diisocyanate, toluene diisocyanate and γ-aminopropyltriethoxysilane is (4.5-5): (2-2.2): (0.3-0.4).

[0041] As a preferred solution, the carbon fiber is chopped carbon fiber.

[0042] As a preferred solution, the average diameter of the chopped carbon fibers is 5 to 8 μm; and the average length of the chopped carbon fibers is 7 to 12 mm.

[0043] The second aspect of the present application provides a preparation process for the above-mentioned wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene, which specifically includes the following steps: S1: Mix the modified graphene nanosheets and the dispersant and add them to deionized water, ultrasonically disperse them into a stable suspension, and then add antibacterial agent, dispersant, antioxidant, stabilizer, softener and cross-linking agent in sequence, and stir at a speed of 100-200rpm for 20-30min after each addition to ensure that all ingredients are evenly mixed to obtain a mixed solution; S2: Stir and mix the polyester fiber and the carbon fiber and impregnate them into the mixed solution, stir and impregnate at a speed of 300-400rpm for 30-35min, and then dry the impregnated fiber at 130-150℃ for 20-25min to remove excess moisture and promote the curing of the coating to obtain a mixed fiber; S3: Ring-spin the mixed fiber into yarn, select a suitable weaving method according to the requirements of the final fabric, adjust the density of the warp and weft yarns to achieve the required fabric thickness and strength, and the mixture is completed.

[0044] The beneficial effects of this application are:

[0045] 1. The present application provides a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene, which not only has good wear resistance and antibacterial properties, but also can further improve its moisture absorption and perspiration, aging resistance, corrosion resistance and other properties, effectively meet the needs of consumers for existing textiles, have more functionality, and have very excellent application prospects.

[0046] 2. The present application provides a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene. The added modified graphene nanosheets can use titanium dioxide as a particle medium to form the synthesis and embedding of framework particles on the surface and side of the nanosheets through group action, thereby realizing a sheet-like composite structure based on graphene nanosheets. The existence of this structure can form a good heterojunction structure. Under the light environment, it can prompt the titanium dioxide particles on the surface to form more hole-electron pairs, and can extend the movement path of electrons and widen the band gap length, thereby allowing holes and electrons to gather for a long time, which not only greatly improves its oxidative antibacterial properties, but also avoids the backflow of electrons, thereby obtaining excellent long-term antibacterial effects during long-term use. In particular, the addition of chopped carbon fibers has significantly improved this effect, and the formed line-surface composite structure has greatly enhanced its connection force under the action of external forces, thereby achieving an improvement in the mechanical properties of the fabric.

[0047] 3. The present application provides a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene. The added modified graphene nanosheets can also form a guiding path for water molecules through the selected specific dispersant and chopped carbon fibers. The dispersant can enhance the surface stability of the modified graphene nanosheets and chopped carbon fibers in the mixed fabric, and when in contact with water, it can guide and adsorb water through a large number of surface hydrophilic groups. The more complex peak and valley surface can form grooves to lock the surface moisture and limit its migration effect, thereby realizing a continuous hydration layer area, accelerating the passage of moisture, and effectively realizing moisture absorption and perspiration, and having excellent hygroscopicity; and the addition of carbon fibers can greatly enhance the surface free radical activity of the modified graphene nanosheets, and limit the penetration of active groups in the fabric coating, thereby effectively protecting the fibers, and obtaining excellent aging resistance and corrosion resistance. DETAILED DESCRIPTION

[0048] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0049] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0050] Example 1

[0051] Example 1 The first aspect provides a wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene. The raw materials are, by mass: 72.5 parts of polyester fiber, 5.2 parts of modified graphene nanosheets, 0.4 parts of antibacterial agent, 2.8 parts of dispersant, 0.8 parts of antioxidant, 1.4 parts of stabilizer, 1.8 parts of softener, 3.2 parts of cross-linking agent, and 9 parts of carbon fiber.

[0052] The fineness of the polyester fiber is 0.8 denier; the average length of the polyester fiber is 45 mm; the cross section of the polyester fiber is a pentagonal cross section; the polyester fiber is purchased from the corresponding specification product sold by Taian Haosong Fiber Co., Ltd. of China.

[0053] The preparation method of modified graphene nanosheets specifically includes the following steps: S1: 7.2 parts of graphene nanosheets and 1.1 parts of titanium dioxide are mixed and added to 200 parts of DMF solution, the temperature is raised to 75°C, 1.8 parts of succinic anhydride are added, and the reaction is kept warm for 2.5 hours. After completion, the pretreated nanosheets are washed, filtered, and dried to obtain pretreated nanosheets; S2: 0.6 parts of titanium dioxide and 2.8 parts of anhydrous aluminum chloride are mixed and added to a mixed solution of DMF and deionized water (the mass ratio of DMF to deionized water is 3:1, a total of 150 parts), and stirred at 120rpm for 12 minutes. Then add a mixed DMF solution of 1.6 parts of terephthalic acid and 1.2 parts of 2-aminoterephthalic acid (60 parts in total), stir at 120rpm for 15min to form a uniform solution, seal the reaction container, heat to 140°C under nitrogen protection, and keep the reaction for 15h; S3: After the reaction is completed, cool naturally to 75°C, then add 1.3 parts of pretreated nanosheets, continue to keep warm for 6h, after the reaction is completed, add triethanolamine to adjust the pH value to 7.8, then filter the product, wash it with deionized water and acetone for 3 times, and then vacuum dry it at 80°C to complete.

[0054] The average particle size of titanium dioxide is 16 nm.

[0055] The graphene nanosheets have 8 to 10 layers and an average lateral size of 4.2 μm, and are purchased from Henan Liugong Graphite Co., Ltd. of China.

[0056] The antimicrobial agent is cetyltrimethylammonium bromide.

[0057] The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine, and the mass ratio of the three is 8.5:2.6:3.6.

[0058] The hydroxyl value of lauryl alcohol polyoxyethylene ether is 180 mgKOH / g, and it was purchased from the MOA-3 product sold by China Hai'an Guo Chemical Co., Ltd.

[0059] The antioxidant was antioxidant 1010.

[0060] The stabilizer is a composition of dibutyltin dilaurate and UV-531, and the mass ratio of the two is 4:1.2.

[0061] The softener is a composition of hexadecyltrimethylammonium chloride, aminosilicone oil and glyceryl stearate, and the mass ratio of the three is 1.2:5.5:0.3.

[0062] The cross-linking agent is a composition of diphenylmethane diisocyanate, toluene diisocyanate and gamma-aminopropyltriethoxysilane, and the mass ratio of the three is 4.8:2.1:0.3.

[0063] The carbon fiber is chopped carbon fiber with an average diameter of 7.5 μm and an average length of 10.5 mm, and is purchased from Shanghai Lishuo Composite Materials Co., Ltd.

[0064] The second aspect of this embodiment provides a preparation process for the above-mentioned wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene, which specifically includes the following steps: S1: Mix the modified graphene nanosheets and the dispersant and add them to deionized water, ultrasonically disperse them into a stable suspension, and then add antibacterial agent, dispersant, antioxidant, stabilizer, softener and cross-linking agent in sequence, and stir at 180rpm for 25min after each addition to ensure that all ingredients are evenly mixed to obtain a mixed solution; S2: Stir and mix the polyester fiber and the carbon fiber and impregnate them into the mixed solution, stir and impregnate at 400rpm for 30min, and then dry the impregnated fiber at 140°C for 22min to remove excess moisture and promote the curing of the coating to obtain a mixed fiber; S3: Ring-spin the mixed fiber into yarn, select a suitable weaving method according to the requirements of the final fabric, adjust the density of the warp and weft yarns to achieve the required fabric thickness and strength, and the mixture is completed.

[0065] Example 2

[0066] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene comprises, by weight, 75 parts of polyester fiber, 4 parts of modified graphene nanosheets, 0.4 parts of antibacterial agent, 2.5 parts of dispersant, 0.8 parts of antioxidant, 1.4 parts of stabilizer, 1.8 parts of softener, 3 parts of cross-linking agent and 10 parts of carbon fiber.

[0067] The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl polyoxyethylene ether and cocamidopropyl betaine, and the mass ratio of the three is 6:4:4.

[0068] The stabilizer is a composition of dibutyltin dilaurate and UV-531, and the mass ratio of the two is 5:1.

[0069] The softener is a composition of hexadecyltrimethylammonium chloride, aminosilicone oil and glyceryl stearate, and the mass ratio of the three is 1.5:5:0.5.

[0070] The cross-linking agent is a composition of diphenylmethane diisocyanate, toluene diisocyanate and gamma-aminopropyltriethoxysilane, and the mass ratio of the three is 4:3:0.6.

[0071] Example 3

[0072] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene comprises, by weight, 70 parts of polyester fiber, 5.5 parts of modified graphene nanosheets, 0.4 parts of antibacterial agent, 3 parts of dispersant, 0.8 parts of antioxidant, 1.4 parts of stabilizer, 1.8 parts of softener, 3.5 parts of cross-linking agent and 8 parts of carbon fiber.

[0073] The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl polyoxyethylene ether and cocamidopropyl betaine, and the mass ratio of the three is 10:2:3.

[0074] The stabilizer is a composition of dibutyltin dilaurate and UV-531, and the mass ratio of the two is 3:1.4.

[0075] The softener is a composition of hexadecyltrimethylammonium chloride, aminosilicone oil and glyceryl stearate, and the mass ratio of the three is 1:6:0.3.

[0076] The cross-linking agent is a composition of diphenylmethane diisocyanate, toluene diisocyanate and gamma-aminopropyltriethoxysilane, and the mass ratio of the three is 5:2:0.3.

[0077] Comparative Example 1

[0078] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene comprises, by weight, 80 parts of polyester fiber, 8.5 parts of modified graphene nanosheets, 0.4 parts of antibacterial agent, 1.5 parts of dispersant, 0.8 parts of antioxidant, 1.4 parts of stabilizer, 1.8 parts of softener, 2.1 parts of cross-linking agent and 9 parts of carbon fiber.

[0079] The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine, and the mass ratio of the three is 5:0:1.

[0080] Comparative Example 2

[0081] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene comprises, by weight, 70.5 parts of polyester fiber, 6.2 parts of modified graphene nanosheets, 0.4 parts of antibacterial agent, 2.8 parts of dispersant, 0.8 parts of antioxidant, 1.4 parts of stabilizer, 1.8 parts of softener, 3.2 parts of cross-linking agent and 9 parts of carbon fiber.

[0082] The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine, and the mass ratio of the three is 2:6:1.

[0083] Comparative Example 3

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that the cross section of the polyester fiber is a triangular cross section.

[0085] Comparative Example 4

[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that the dispersant is a composition of cetearyl alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate, and the mass ratio of the two is 3:1.

[0087] Comparative Example 5

[0088] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified graphene nanosheet specifically comprises the following steps: S1: 9.5 parts of graphene nanosheets and 0.5 parts of titanium dioxide are mixed and added to 300 parts of DMF solution, the temperature is raised to 75°C, 2.5 parts of succinic anhydride are added, and the reaction is kept warm for 2.5 hours. After completion, washing, filtering, and drying are performed to obtain pretreated nanosheets; S2: 0.2 parts of titanium dioxide and 2.8 parts of anhydrous aluminum chloride are mixed and added to a mixed solution of DMF and deionized water (the mass ratio of DMF to deionized water is 3:1, a total of 150 parts), 1 The mixture was stirred at 20 rpm for 12 min, and then a mixed DMF solution of 1.6 parts of terephthalic acid and 1.2 parts of 2-aminoterephthalic acid (60 parts in total) was added, and the mixture was stirred at 120 rpm for 15 min to form a uniform solution. The reaction vessel was sealed, and the temperature was raised to 140°C under nitrogen protection, and the reaction was kept warm for 15 hours. S3: After the reaction was completed, the mixture was naturally cooled to 75°C, and then 1.3 parts of pretreated nanosheets were added, and the temperature was kept warm for 6 hours. After the reaction was completed, triethanolamine was added to adjust the pH value to 7.8, and the product was filtered, washed with deionized water and acetone for 3 times, and then vacuum dried at 80°C to complete the reaction.

[0089] Comparative Example 6

[0090] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified graphene nanosheets specifically comprises the following steps: S1: 7.2 parts of graphene nanosheets and 1.1 parts of titanium dioxide are mixed and added to 200 parts of DMF solution, the temperature is raised to 75°C, 1.8 parts of succinic anhydride are added, and the reaction is kept warm for 2.5 hours. After completion, washing, filtering, and drying are performed to obtain pretreated nanosheets; S2: 1.5 parts of titanium dioxide and 2.8 parts of anhydrous aluminum chloride are mixed and added to a mixed solution of DMF and deionized water (the mass ratio of DMF to deionized water is 3:1, a total of 150 parts), 1 The mixture was stirred at 20 rpm for 12 min, and then a mixed DMF solution of 1.6 parts of terephthalic acid and 1.2 parts of 2-aminoterephthalic acid (60 parts in total) was added, and the mixture was stirred at 120 rpm for 15 min to form a uniform solution. The reaction vessel was sealed, and the temperature was raised to 140°C under nitrogen protection, and the reaction was kept warm for 15 hours. S3: After the reaction was completed, the mixture was naturally cooled to 75°C, and then 0.5 parts of pretreated nanosheets were added, and the temperature was kept warm for 6 hours. After the reaction was completed, triethanolamine was added to adjust the pH value to 7.8, and the product was filtered, washed with deionized water and acetone for 3 times, and then vacuum dried at 80°C to complete the reaction.

[0091] Comparative Example 7

[0092] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 45 nm. The number of layers of graphene nanosheets is 15 to 20, and the average lateral size is 6.5 μm, which is purchased from Henan Liugong Graphite Co., Ltd. of China.

[0093] Performance Evaluation

[0094] Abrasion resistance test: The abrasion resistance test was carried out on the fabrics obtained in the embodiments and comparative examples with reference to the standard ASTM D3383. The grinding wheel was H18 and the number of tests was 5000. The weight loss percentage before and after the test was recorded. The test value was the average value of 50 tests and recorded in Table 1. The surface state of the fabric after the test was recorded. If there was no color change, no fuzzing, no pilling, and no obvious wear, it was recorded as qualified, otherwise it was unqualified. Each group was tested 50 times, and the qualified rate was recorded in Table 1.

[0095] Antibacterial test: The antibacterial test was carried out on the fabrics prepared in the embodiment and the comparative example according to the standard AATCC 100. The test strain was Staphylococcus aureus, and the concentration of the bacterial suspension was 10 5 CFU / mL, 37°C, 24 hours, to obtain the final antibacterial rate results, the test value is the average of 10 tests and recorded in Table 1.

[0096] Hygroscopicity test: The fabrics prepared in the examples and comparative examples were tested for moisture regain according to standard ISO 139:2017. The test values ​​were averaged over 10 tests and recorded in Table 1.

[0097] Aging corrosion resistance test: The fabrics prepared in the examples and comparative examples were made into 25 mm × 100 mm long strip fabric samples, and 5 wt% NaCl was sprayed on the inclined surface at 62 ± 2 ° C and 80 ± 2% humidity. The spraying rate was 1 mL / 80 cm 2 / h, test for 72h, take out after 72h to observe whether there is damage, pilling, fuzzing and discoloration. If there is any, it is recorded as unqualified, otherwise it is qualified. Each group is tested 50 times, and the qualified rate is recorded in Table 1.

[0098] Table 1 Performance test results

[0099]

[0100] It can be seen from the embodiments and comparative examples of the present application and the data results in Table 1 that embodiments 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of wear resistance, antibacterial properties, moisture absorption and perspiration resistance, and aging corrosion resistance. This is mainly due to the combined effect of the modified graphene nanosheets, specific dispersant combinations, and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and for solving technical problems.

Claims

1. A wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene, characterized in that: The raw materials are, by weight: 60-80 parts of polyester fiber, 2-6 parts of modified graphene nanosheets, 0.3-0.8 parts of antibacterial agent, 2-4 parts of dispersant, 0.5-1 parts of antioxidant, 1-2 parts of stabilizer, 1-3 parts of softener, 2-4 parts of crosslinking agent, and 5-15 parts of carbon fiber; The polyester fiber has a fineness of 0.5 to 1.5 denier; The average length of the polyester fiber is 30 to 60 mm; The cross section of the polyester fiber is a Y-shaped cross section or a pentagonal cross section; The preparation method of the modified graphene nanosheet is specifically The following steps are involved: S1: Mix graphene nanosheets and titanium dioxide and add them to DMF solution, heat to 70-75°C, add succinic anhydride and keep warm for 2-3 hours, wash and filter after completion, and dry to obtain pretreated nanosheets; S2: titanium dioxide and anhydrous aluminum chloride are mixed and added to a mixed solution of DMF and deionized water, and stirred at 100-120 rpm for 10-15 min, and then a mixed DMF solution of terephthalic acid and 2-aminoterephthalic acid is added, and stirred at 100-120 rpm for 10-15 min to form a uniform solution, and the reaction container is sealed, and the temperature is raised to 130-150° C. under nitrogen protection, and the temperature is kept for 14-16 hours; S3: after the reaction is completed, it is naturally cooled to 70-80° C., and then the pretreated nanosheets are added, and the temperature is kept for 4-6 hours. After the reaction is completed, triethanolamine is added to adjust the pH value to 7.5-8, and then the product is filtered, and the deionized water and acetone are washed 2-3 times in a cycle, and then vacuum dried at 70-80° C. to complete the product; In S1, the mass ratio of graphene nanosheets, titanium dioxide and succinic anhydride is (6-8): (0.8-1.4): (1.5-2); in S2 and S3, the mass ratio of titanium dioxide, anhydrous aluminum chloride, terephthalic acid, 2-aminoterephthalic acid and pretreated nanosheets is (0.5-0.8): (2.5-3.5): (1.4-2): (1-1.4): (1-2).

2. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 1, characterized in that: The mass ratio of the polyester fiber, the modified graphene nanosheet and the carbon fiber is (70-75): (4-5.5): (8-10).

3. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 2, characterized in that: The mass ratio of the modified graphene nanosheet, the dispersant and the cross-linking agent is (4-5.5): (2.5-3): (3-3.5).

4. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 3, characterized in that: The average particle size of the titanium dioxide is 10 to 20 nm.

5. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 4, characterized in that: The number of layers of the graphene nanosheet is 5 to 10; the lateral size of the graphene nanosheet is 3 to 5 μm.

6. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 5, characterized in that: The antibacterial agent is at least one of silver chloride, zinc oxide, hexadecyltrimethylammonium bromide, potassium sorbate and sodium benzoate.

7. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 6, characterized in that: The dispersant is a composition of polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine; the mass ratio of the polyethylene glycol fatty acid ester, lauryl alcohol polyoxyethylene ether and cocamidopropyl betaine is (6-10): (2-4): (2-4).

8. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 7, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 1076 , antioxidant 168 , or antioxidant 626 .

9. The wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to claim 8, characterized in that: The carbon fiber is chopped carbon fiber; the average diameter of the chopped carbon fiber is 5 to 8 μm; the average length of the chopped carbon fiber is 7 to 12 mm.

10. A process for preparing the wear-resistant and antibacterial school uniform fabric based on polyester fiber and graphene according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Mix the modified graphene nanosheets and the dispersant and add them into deionized water, ultrasonically disperse them into a stable suspension, then add the antibacterial agent, dispersant, antioxidant, stabilizer, softener and cross-linking agent in sequence, stir at 100-200 rpm for 20-30 min after each addition to ensure that all the ingredients are evenly mixed to obtain a mixed solution; S2: Stir and mix the polyester fiber and the carbon fiber and impregnate them into the mixed solution, stir and impregnate at 300-400 rpm for 30-35 min, then dry the impregnated fiber at 130-150° C. for 20-25 min to remove excess moisture and promote the curing of the coating to obtain a mixed fiber; S3: Ring-spin the mixed fiber into yarn, select a suitable weaving method according to the requirements of the final fabric, adjust the density of the warp and weft yarns to achieve the required fabric thickness and strength, and the mixture is completed.

Citation Information

Patent Citations

  • Aluminum-based metal organic frame-graphene oxide composite material, as well as preparation method and application thereof

    CN106669612A

  • Wear resistant and antistatic polyamide composite material and preparation method thereof

    CN106967293A

  • Uvioresistant enhancement stage PE / PET composite elastic short fiber and preparing method thereof

    CN111748868A

  • Titanium dioxide-based metal organic framework compound as well as preparation method and application thereof

    CN114177948A

  • Antibacterial terylene woven gray fabric and production process thereof

    CN114182524A